Does a shorter length of hospital stay affect the outcome and costs of hysterectomy in southern England?. Issue 5 (October 1996) - Clarke, A; Rowe, P; Black, N
Abstract : STUDY OBJECTIVE: To see whether a shorter postoperative length of stay (LOS) for a major procedure, abdominal hysterectomy for benign conditions, was associated with health outcome, the use of formal and lay care after discharge, cost, and satisfaction. DESIGN: Prospective cohort study. SETTING: Three hospitals in London and three in Hertfordshire and Bedfordshire. PATIENTS: A total of 363 women undergoing total abdominal hysterectomy with or without oophorectomy: 112 with a short postoperative LOS (five days or less) and 251 with a standard LOS (six days or more). MAIN OUTCOME MEASURES: Wound infection within 10 days and six weeks; change in general health status (Nottingham health profile) after six weeks; general health and change in social activity (lifestyle index) three months after surgery. Mean cost difference for hospitals, use of formal and lay care after discharge, and patient satisfaction. RESULTS: Short LOS was associated with benefits: a lower risk of wound infection in the first 10 days (odds ratio 0.44; p = 0.03) and no deterioration in physical mobility (measured using the NHP) after six weeks- and with adverse outcomes: constipation six weeks later (OR 0.48; p < 0.001) and moderate or severe urinary symptoms six weeks (OR 0.69; p < 0.004) and three months (OR 0.65; p < 0.008) later. On multivariate analysis, the only outcome to remain significantly associated with LOS was physical mobility after six weeks (p = 0.024). There was no significant difference between short and standard stay women as regards their use of formal or lay care after discharge from hospital. The mean cost of hospital care was Pounds251 (in 1992) less for short than for standard stay patients. Most women (73% at six weeks) felt their LOS was appropriate. Short stay women were more likely to feel it was too short, though the difference was not statistically significant. CONCLUSIONS: Short postoperative stays do not seem to be associated with any adverse outcomes and result in modest financial saving to the health service. There is potential for greater use of early discharge.